Analisis Performansi Jaringan Fiber Optic Pada Penyambungan Single-Mode Ke Multi-Mode Provider Xl Menggunakan Perangkat Temporary - Silalahi, Rhendy Theopilus; Sari, Linna Oktaviana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Fiber optic network (FO) is currently one of the telecommunications network transmissions widely used by operators to meet the needs of telecommunication services. FO is able to transmit data quickly. This is because the FO has a large bandwidth and has a small attenuation. Behind the advantages, the FO also has a disadvantage, namely the FO transmission does not always meet the damping standards provided by the operator. Such as fiber optic attenuation (attenuation loss), splice loss, connector attenuation (connector loss), bending loss, coupling loss and other attenuation. In general, operators use the single mode – single mode (SM) FO connection method. This research uses single mode – multi mode method. This research can help operators in performing maintenance and troubleshooting by analyzing power link bugdet on single mode – multi mode (MM) FO connection to improve FO network performance, so that operators can compete with other telecommunications service providers.Keywords : Power link budget, loss, single-mode, multy-mode, fiber optic